2021
DOI: 10.3389/phrs.2021.1604212
|View full text |Cite|
|
Sign up to set email alerts
|

Reviewing School Uniform through a Public Health Lens: Evidence about the Impacts of School Uniform on Education and Health

Abstract: This study uses a public health lens to review evidence about the impacts of wearing a school uniform on students’ health and educational outcomes. It also reviews the underlying rationales for school uniform use, exploring historical reasons for uniform use, as well as how questions of equity, human rights, and the status of children as a vulnerable group are played out in debates over school uniforms. The literature identified indicates that uniforms have no direct impact on academic performance, yet directl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 88 publications
(138 reference statements)
1
20
1
Order By: Relevance
“…There is, of course, a wide and at-times heated debate about the advantages, disadvantages, cost-effectiveness of school uniforms for children and young people and, for our purposes, in Catholic schools (Ansari et al, 2021;Brunsma, 2004;Reidy, 2021). While there is limited space to engage with these debates and the area of Catholic school uniform is under researched, it is worth observing a number of points.…”
Section: School Uniformmentioning
confidence: 99%
“…There is, of course, a wide and at-times heated debate about the advantages, disadvantages, cost-effectiveness of school uniforms for children and young people and, for our purposes, in Catholic schools (Ansari et al, 2021;Brunsma, 2004;Reidy, 2021). While there is limited space to engage with these debates and the area of Catholic school uniform is under researched, it is worth observing a number of points.…”
Section: School Uniformmentioning
confidence: 99%
“…School uniforms have an important social context; in fact, in New Zealand, it is a reason why students choose their schools (1), but in general, uniforms have been adopted as strategies by principals and governments to improve educational test scores and student behavior (2,3). Indeed, several studies have suggested that traditional uniforms remove social differences, increase security, reduce violence, improve school climate and discipline, promote social responsibility, and improve academic achievement (2)(3)(4)(5)(6)(7)(8). However, findings on this matter are highly sparse and heterogeneous and seem to be dependent on the population studied, age, race, educational context, and socioeconomic status (2, 3, 6, 9, 10), and the aforementioned features have not been proven yet (3,6,7,9).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several studies have suggested that traditional uniforms remove social differences, increase security, reduce violence, improve school climate and discipline, promote social responsibility, and improve academic achievement (2)(3)(4)(5)(6)(7)(8). However, findings on this matter are highly sparse and heterogeneous and seem to be dependent on the population studied, age, race, educational context, and socioeconomic status (2, 3, 6, 9, 10), and the aforementioned features have not been proven yet (3,6,7,9). Given that most evidence about this research issue comes from developed countries, ascertaining uniforms' influence in a less advantageous social context (e.g., in a Latin-American country such as Chile) could give us more insight into this public matter.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations